Please give step by step answer!! Thanks!
first put the -1 into the 3x and -4, so it looks like 2-3x+4=2x-9, then combine 2 and 4, (-3x+6=2x-9), then subtract 2x from both sides (-5x+6=-9) then subtract 6 to both sides so -5x=-15, then divide by 5 so x=3 hope this helps!! sorry i messed up the first time
Simplify both sides of the equation 2-(3x-4)=2x-92+-1(3x-4)=2x-9Distribute the negative sign 2+-1(3x)+(-1)(-4)=2x-92+-3x+4=2x-92+-3x+4=2x+-9Combine like terms (-3x)+(2+4)=2x-9-3x+6=2x-9Subtract 2x from both sides -3x+6-2x=2x-9-2x-5x+6=-9Subtract 6 from both sides -5x+6-6=-9-6-5x=-15Divide both sides by -5-5x/5=-15/-5x=3
I hope that's help !